Trust, fear, stigma and disruptions: community perceptions and experiences during periods of low but ongoing transmission of Ebola virus disease in Sierra Leone, 2015 - Nuriddin, Azizeh (BMJ Glob Health, 2018)
Social mobilisation and risk communication were essential to the 2014–2015 West African Ebola response. By March 2015, >8500 Ebola cases and 3370 Ebola deaths were confirmed in Sierra Leone. Response efforts were focused on ‘getting to zero and staying at zero’. A critical component of this plan was to deepen and sustain community engagement. Several national quantitative studies conducted during this time revealed Ebola knowledge, personal prevention practices and traditional burial procedures improved as the outbreak waned, but healthcare system challenges were also noted. Few qualitative studies have examined these combined factors, along with survivor stigma during periods of ongoing transmission. To obtain an in-depth understanding of people’s perceptions, attitudes and behaviours associated with Ebola transmission risks, 27 focus groups were conducted between April and May 2015 with adult Sierra Leonean community members on: trust in the healthcare system, interactions with Ebola survivors, impact of Ebola on lives and livelihood, and barriers and facilitators to ending the outbreak. Participants perceived that as healthcare practices and facilities improved, so did community trust. Resource management remained a noted concern. Perceptions of survivors ranged from sympathy and empathy to fear and stigmatisation. Barriers included persistent denial of ongoing Ebola transmission, secret burials and movement across porous borders. Facilitators included personal protective actions, consistent messaging and the inclusion of women and survivors in the response. Understanding community experiences during the devastating Ebola epidemic provides practical lessons for engaging similar communities in risk communication and social mobilisation during future outbreaks and public health emergencies.